Phosphoprotein Gene of Wild-Type Rabies Virus Plays a Role in Limiting Viral Pathogenicity and Lowering the Enhancement of BBB Permeability - Long, Teng; Zhang, Boyue; Fan, Ruqi; Wu, Yuting; Mo, Meijun; Luo, Jun; Chang, Yiran; Tian, Qin; Mei, Mingzhu; Jiang, He; Luo, Yongwen; Guo, Xiaofeng (Frontiers in Microbiology, 2020)
Enhancement of blood-brain barrier (BBB) permeability is necessary for clearing virus in central nerve system. It has been reported that only laboratory-attenuated rabies virus (RABV) induces inflammatory response to lead BBB transient breakdown rather than wild-type (wt) strains. As component of ribonucleoprotein, phosphoprotein (P) of RABV plays a key role in viral replication and pathogenicity. To our knowledge, the function of RABV P gene during RABV invasion was unclear so far. In order to determine the role of RABV P gene during RABV infection, we evaluated the BBB permeability in vivo after infection with wt RABV strain (GD-SH-01), a lab-attenuated RABV strain (HEP-Flury) and a chimeric RABV strain (rHEP-SH-P) whose P gene cloned from GD-SH-01 was expressed in the genomic backbone of HEP-Flury. We found that rHEP-SH-P caused less enhancement of BBB permeability and was less pathogenic to adult mice than GD-SH-01 and HEP-Flury. In effort to investigate the mechanism, we found the replication of rHEP-SH-P has been limited due to the suppressed P protein expression and induced less response to maintain BBB integrity. Our data indicated that the P gene of wild-type RABV was a potential determinant in hampering viral replication in vivo which kept BBB integrity. These findings provided an important foundation for understanding the viral invasion and development of novel vaccine.